A population structure analysis of Candida dubliniensis using multilocus sequence typing and an investigation of the molecular mechanism(s) of clade-specific resistance to 5-fluorocytosine - McManus, Brenda (Trinity College (Dublin, Ireland). School of Dental Science, 2009)
Candida dubliniensis shares many phenotypic and genetic characteristics with its closest relative, Candida albicans, which most likely delayed the identification and subsequent classification of C. dubliniensis as a distinct taxon. Previous population structure analyses of C. dubliniensis were based on DNA fingerprinting using the species-specific probe Cd25, and sequence analysis of the internal transcribed spacer (ITS) region of the ribosomal gene cluster. These studies showed that C dubliniensis is comprised of three major clades (Cd25 groups I- III) comprising four distinct ITS genotypes (1-4). Multilocus sequence typing (MLST) has proved useful for investigating the population biology of C. albicans, identifying many distinct clades. In the present study, MLST was used to investigate the population structure of C. dubliniensis for the first time. Combinations of ten loci previously tested for MLST analysis of C. albicans were assessed for their discriminatory ability with epidemiologically unrelated C. dubliniensis isolates from diverse geographic locations, including representative isolates of the previously identified three Cd25-deflned major clades and four ITS genotypes. UPGMA dendrograms generated using the data from these loci revealed a population structure which supports that previously suggested by Cd25 fingerprinting and ITS genotyping, identifying three main MLST clades (termed C1-C3) comprising four ITS genotypes. Application of a common MLST scheme to C. dubliniensis and C. albicans revealed that the population structure of C. dubliniensis is significantly less divergent than that of C. albicans. On the basis of the highest number of genotypes per variable base the following eight loci are recommended for MLST analysis of C. dubliniensis', AATlb, ACCl, ADPl, PMlb, RPN2, ALAI, exVPSlS, and exZWFlb. When 14 avian-excrement-associated C. dubliniensis isolates recovered from two separate locations in Ireland, approximately 150 km apart, and 36 C. dubliniensis isolates recovered from humans in Ireland were compared using these recommended loci, all 50 isolates were found to belong to MLST clade Cl and belonged to ITS genotype 1. However, 13/14 of avian- excrement-associated isolates were found to be genetically distinct from the human isolates. Six new diploid sequence types (DSTs) were identified in 13 of 14 avian-associated-excrement isolates. The remaining isolate was identical to a human isolate, suggesting that transmission may occur between humans and birds. In total, the C. dubliniensis MLST scheme has identified 37 DSTs from the 78 human and avian-associated C. dubliniensis isolates examined to date.
Keywords: Dental Science, Ph.D.; Ph.D. Trinity College Dublin